Kepuasan Kerja Tenaga Medis pada Era Jaminan Kesehatan Nasional - Arifin, Nur Fadhilah; A. Pasinringi, Syahrir; Palu, Basir (Media Kesehatan Masyarakat Indonesia, 2018)
Medical personnel as the spearhead of hospital services deeply feel the change in health care system in National Health Insurance (NHI) era that implements the system of quality control and cost control. The aim of the research was to explore the employee satisfaction of medical personnel in the era of the National Health Insurance in Regional Public Hospital of Sinjai. The research was a descriptive qualitative study with a case study approacch. The informants were medical personnel as functional personnel. To obtain additional information as comparison, the researcher also interviewed the director, the head of service and nursing unit, the head of financial sub-unit, and Sisrute officials in Regional Public Hospital of Sinjai. The data were obtained through indepth interview, observation and documentation. The result of the research indicate the service system in the era of National Health Insurance is good, but its implementation has not runas it is expected. The cooperation between BPJS and Regional Public Hospital of Sinjai is considered slow and inconsistent and sometimes the problem solving is not followed up. Medical personnel in Regional Public Hospital of Sinjai is satisfied with transparency of medical service division, but the number of Ina CBGs packages are still under the standar and time of payment of medical service is late.